FORMATION OF SCIENTIFIC POTENTIAL AND QUALITY OF LIFE IN SINGLE INDUSTRY TOWNS OF THE REPUBLIC OF KAZAKHSTAN (THE CASE OF ZHEZKAZGAN CITY) - Sagintayeva Saule Savetovna,; Zhanbayev Rinat Abdykadyrovich,; Temirbaeva Gulnara Rapykovna,; Abildina Ainur Shahizadina,; Maria Sergeevna Turovskaya, (Scientific Journal of Pedagogy and Economics, 2020)
Тhe development of methodological approaches and organizational measures to solve the problems of increasing level and quality of life of the population in single-industry towns based on an analysis of the status and development trends of the scientific potential. The methods which were used in this study are logical, statistical analysis and synthesis. The new idea is that the indicator of improving the quality of life of the population in depressed regions is staffing of scientific and innovative activities. The results of this study can be further developed to measure the general level of the status of scientific personnel’strainingand the conditions for its growth in the general context of improving the quality of life of the population. A new approach has been formed in the methodology of measuring the level and quality of life of the population. An organizational mechanism for the interaction of science and production is proposed, combining the scientific potential of the university and the industrial city-forming enterprise. The results and conclusions of the study can be used by territorial and state economic management bodies in elaboration of economic development programs and in determining the level and quality of life of the population.